2019
DOI: 10.1002/ajim.23072
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of health service use following work‐related injury and illness in Australian truck drivers: A latent class analysis

Abstract: ObjectivesTo identify patterns of health service use (HSU) in truck drivers with work‐related injury or illness and to identify demographic and work‐related factors associated with patterns of care.MethodAll accepted workers’ compensation claims from truck drivers lodged between 2004 and 2013 in Victoria were included. Episodes of HSU were categorised according to practitioner type. Latent class analysis was used to identify the distinct profiles of users with different patterns of HSU. Multinomial logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…Other studies have reported statistically significant relationships between opioid use and Workers’ Compensation Claims 35,36 . Few studies assessed relationships between other factors and Workers’ Compensation Claims among truck drivers 37–40 . Although, research has demonstrated the association between opioid use and increased unsafe driver actions among commercial drivers, 26 the overarching literature investigating opioid use in the truck driver population is scant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported statistically significant relationships between opioid use and Workers’ Compensation Claims 35,36 . Few studies assessed relationships between other factors and Workers’ Compensation Claims among truck drivers 37–40 . Although, research has demonstrated the association between opioid use and increased unsafe driver actions among commercial drivers, 26 the overarching literature investigating opioid use in the truck driver population is scant.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Few studies assessed relationships between other factors and Workers' Compensation Claims among truck drivers. [37][38][39][40] Although, research has demonstrated the association between opioid use and increased unsafe driver actions among commercial drivers, 26 the overarching literature investigating opioid use in the truck driver population is scant. Thus, further investigation of the relationship between prescription drug use and commercial driving outcomes is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The second includes all other prescription medicines (other medicines). Pain and anti-depressant medicines will be examined in sub-categories such as opioid strength [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Safe Work Australia has identified truck driving as a priority area for health and safety reform due to the high number of fatalities, injuries and illnesses that occurs in this occupational group [ 1 ]. Truck drivers are at greater risk of work-related injury and disease even compared with other groups of drivers (i.e., bus drivers, automobile drivers, delivery drivers, rail drivers), with an elevated rate of 70.3 claims per 1000 workers per year [ 2 ]. Additionally, the relative risk of workers’ compensation claims increases with age [ 3 ].…”
Section: Introductionmentioning
confidence: 99%